Pendidikan Karakter di Era Merdeka Belajar Melalui Telaah Naskah Serat Wedhatama (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2023)
This study aims to explore the character values ​​contained in the old manuscript of Serat Wedhatama to shape the character of students as the next generation of young people to continue the life of the nation. The method used was a qualitative descriptive method, with the data source taken from Serat Wedhatama by KGPAA Mangkunegara IV. The technique used was document analysis. The results of data analysis showed that every stanza of the song in the Serat Wedhatama has character values ​​that can be used as a mean to shape the character of students as the young generation that continue the life of the nation. In the era of independent learning, a character is an important thing that must get attention. For this reason, this research was conducted to contribute to shaping the character of the younger generation.
Keywords: Character Education; Freedom Learning; Serat Wedhatama